Outcomes of FETD versus UBE in the treatment of L5S1 foraminal stenosis: A comparative study - Yao-Chun Yang; Min-Hong Hsieh; Jui-Teng Chien; Keng-Chang Liu; Chang-Chen Yang (Heliyon, 2024)
Background: The L5S1 level exhibits unique anatomical features compared with other levels. This makes minimally invasive surgery for L5S1 foraminal stenosis (FS) challenging. This study compared the surgical outcomes of full endoscopic transforaminal decompression (FETD) and unilateral biportal endoscopy with the far-lateral approach (UBEFLA) in patients with L5S1FS. Methods: In this retrospective study, 49 patients with L5S1FS were divided into two groups. Of these, 24 patients underwent FETD, 25 patients underwent UBEFLA. The study assessed demographic data, leg pain visual analog scale (VAS) score, back pain VAS score, Oswestry Disability Index (ODI), modified MacNab outcome scale, and radiographic parameters including postoperative lateral facet preservation (POLFP). Results: The Mann-Whitney U test revealed that the UBEFLA group exhibited a higher VAS score for back pain at one week after the operation, whereas the FETD group exhibited a higher leg pain VAS score 6 weeks after the operation. All four undesired MacNab outcomes in the FETD group were attributed to residual leg pain, whereas all five undesired MacNab outcomes in the UBEFLA group were due to recurrent symptoms. Radiographically, the FETD group exhibited greater POLFP. Conclusions: When L5S1FS is performed, there may be challenges in adequately clearing the foraminal space in FETD. On the other hand, UBEFLA allowed for a more comprehensive clearance. However, this advantage of UBEFLA was associated with spinal instability as a future outcome.